Cover Feature: Naphthalenediimide (NDI)‐Conjugated Foldable Polyurethanes: Impact of Chromophoric Location on Hierarchical Supramolecular Assembly and Conductivity (ChemNanoMat 8/2018). Issue 8 (18th July 2018) - Mukherjee, Anurag; Sakurai, Tsuneaki; Seki, Shu; Ghosh, Suhrit
Abstract : A n‐type semiconducting naphthalene‐diimide (NDI)‐appended foldable polyurethane adopts a pleated structure in non‐polar solvent by intra‐chain H‐bonding and π‐stacking which grows to micrometer long fluorescent nanowires by assembly of multiple foldamers. Such elegant hierarchical assembly generates a percolated pathway for highly effective electron transport as evident from the estimated high charge carrier mobility of 3 × 10 –3 cm 2 V –1 s –1 . More information can be found in the Full Paper by Shu Seki, Suhrit Ghosh et al. onpage 860 in Issue 8, 2018 (DOI:10.1002/cnma.201800220 ).